Digital Romanticism in the Age of Neo-Luddism: the Romantic Circles Experiment - Jones, Steven (Romanticism on the Net)

(untitled) (Université de Montréal, 2006)
AbstractThe Romantic Circles Website, along with a number of other major projects in digital Romanticism, came online around 1995, a historical moment that also saw the emergence of neo-Luddism, in part as a reaction to the techno-hype of the Internet boom. At the time. neo-Luddites often claimed as a precedent the original historical Luddism of 1811-16, but they usually also Romanticized that collective labor subculture to fit their own late-twentieth-century ideas of “technology.” This essay looks back at the interlinked assumptions in the air around 1995–neo-Luddite and Romantic–as the context out of which Romantic Circles defined its own engaged experiment in technology. Iw ill cite specific examples of digital technologies from our first year (two editions about technology, including the technology of texts), and one from our most recent year (an experiment in podcasting), in order to explain how we at Romantic Circles have attempted to work at the crossroads of Romanticism and technology, while stubbornly refusing to play the role of "natural Luddites,"